PENGARUH CAR, LDR, ROA, DAN INFLASI TERHADAP NPL PADA BANK UMUM KONVENSIONAL - Dinda Permatasari; Dwi Ermayanti Susilo (Value : Jurnal Manajemen dan Akuntansi, 2023)
The banking world is currently vulnerable to the challenges of the global recession threat, this will result in a high level of  NPL. NPL is a parameter of a bank's asset health that is calculated based on key financial ratios. The NPL used by banks is the adjusted net NPL. NPL assessment is an asset quality assessment that reflects the adequacy of credit risk management. NPLs are an indication of problems that occur within the bank that have a negative impact on the bank if not resolved immediately. NPLs will cause a bank's capital to decrease so that lending for the next period can be affected. The purpose of this study was to determine the effect of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Return On Asset (ROA), Inflation on Non Performing Loan (NPL) at Conventional Commercial Banks listed on the IDX in 2020-2022. This study uses quantitative methods with secondary data obtained from the financial statements of Conventional Commercial Banks. The population in this study was 42 Conventional Commercial Banks. The sampling method for this study was purposive sampling which resulted in 29 Conventional Commercial Banks. The results of this study indicate that the CAR, LDR, and Inflation variables have no effect on NPL, while the ROA variable has a negative and significant effect on NPL. Keywords: CAR, LDR, ROA, Inflasi, NPL